2007
DOI: 10.1117/12.746805
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and monitoring of photomask edge effects

Abstract: An experimental technique for quantitatively characterizing edge effect contributions in transmission through thick photomasks is described and evaluated through electromagnetic simulation. The technique consists of comparing the 0 th order transmission for various duty cycles to the expected experimental behavior from a thin mask model. The real electric field component from the edges is proportional to the shift in the position of the minimum energy in the 0 th order field away from the expected thin mask lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…11 When examining the intensity of the 0 th order transmission the 0 o and 180 o phase regions cancel each other out. Due to transmission imbalance in the two regions, by changing the duty cycle, we are able to find the maximum cancellation between the 0 o and 180 o areas.…”
Section: Transmission Intensity Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…11 When examining the intensity of the 0 th order transmission the 0 o and 180 o phase regions cancel each other out. Due to transmission imbalance in the two regions, by changing the duty cycle, we are able to find the maximum cancellation between the 0 o and 180 o areas.…”
Section: Transmission Intensity Methodsmentioning
confidence: 98%
“…11 Boundary layer (BL) modeling of edge effects is particularly appealing due to the natural extension for inclusion into OPC and pattern matching. 12 This paper presents an expansion of this method to off-axis illumination, alternate mask stacks, and 3D mask geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity = |E| 2 , and with the math illustrated in Eqns. (4)(5)(6)(7)(8), we obtain a composite match factor compromised of the unaberrated airy function match and the spillover function. The composite match factor incorporates the influence of neighboring features, aberrations, and their complex interaction.…”
Section: Complex Interactionmentioning
confidence: 99%
“…5,6 This paper focuses on the latter because BL modeling allows us to represent the errors as additional transmission regions on the mask layout, whereas DDM does not produce layout based corrections. This makes pattern matching, 7 a fast-CAD method for hot spot detection or design optimization, possible for EMF analysis.…”
Section: Introduction: Emf Effectsmentioning
confidence: 99%
“…Mask edge effects are growing fourth challenge that spans both DUV and EUV. Electromagnetic studies of transmission through ATT-PSM by Marshal Miller [57] have found that the mask edges themselves produce imaginary or out of phase components on each edge as well as an effective bias toward the absorber. This is typically equivalent to a 0.1λ (20 nm) wide strip of quadrature phase electric field of the strength of the clear field at each mask edge.…”
Section: Current Simulation Challengesmentioning
confidence: 99%